Detection of groundwater and soil contamination by hydrocarbons using radon as a tracer - Galhardi, Juliana Aparecida [UNESP]; Bonotto, Daniel Marcos [UNESP]; Barbosa, Eder Queiroz [UNESP] (My University, 2015)
Subsurface contamination with hydrocarbons as non-aqueous phase liquid (NAPL) is one of the most common environmental impact associated with fuel leak in gas station areas and can represent a health human problem due to the formation of long-term sources of groundwater contamination. Techniques to localize the contaminated areas and identify the hydrocarbon sources are necessary in order to properly choose the process of soil and groundwater remediation. The radon gas (222Rn), a natural component of groundwater continually produced by the 226Ra decay in the 238U decay series, has been used as a tracer to detect and quantify the NAPL contamination. Radon, which has high affinity with organic matter, tends to accumulate at the interface between the water and the NAPL. The magnitude of the decrease in its activity concentration through the aquifer can be used to localize contamination plumes and also to estimate the saturation degree of the aquifer pores by hydrocarbon. Field tests have proved the efficiency of this method in two municipalities in the State of São Paulo, Brazil, where the groundwater contamination by NAPL is the most recurring and detected environmental problem associated with industrial activities. In the city of Santa Bárbara d'Oeste, a tendency of positive correlation between radon and dissolved hydrocarbon (BTEX-benzene, etilbenzene, toluene and xilene) was found in groundwater sampled in three gas stations where occurred tanks leaks, suggesting that the presence of dissolved hydrocarbons can increase the radon concentration in water, due to its afinity with this phase. In the city of Rio Claro, the investigation focused on the presence of radon and volatile organic compounds (VOCs) in soil gases providing from a gas station where occurred a fossil fuel leak. The results indicated a negative spatial correlation between the 222Rn and VOCs, demonstrating that the presence of a hydrocarbon residual phase in the aquifer can trap the radon, culminating in its decrease in the soil gas. These methods, which require less time and costs than others, are useful for the detection of residual contamination and dissolved hydrocarbon plumes in groundwater.
Keywords: Aquifer contamination; Groundwater; Hydrocarbons; Radon